Theoretical investigations of band alignments and SnSe BSF layer for low-cost, non-toxic, high-efficiency CZTSSe solar cell. (15th September 2021) - Prabhu, Sudheendra; Pandey, Sushil Kumar; Chakrabarti, Subhananda
Highlights: CZTSSe as absorber layer and zinc oxide compounds as buffer layers are analysed. SnSe as BSF layer is used for improving the conversion efficiency. Ni as back contact and AZO as window layer are used for optimum performance. Abstract: In this work, a numerical simulation approach is utilized using SCAPS-1D software to model, modify, optimize, and evaluate the CZTSSe solar cell structure. For the CZTSSe solar cell, one possible reason hindering the performance is improper band alignment between the absorber and the buffer layers. With conventional CdS as a buffer layer, having a fixed bandgap, tuning the band alignment is impossible. To overcome this issue, Cd-free zinc oxide-based compounds Zn(O1-x Sx ), Zn1-x Snx O, and Zn1-x Mgx O are explored as buffer layers, and their performance is evaluated. Using their composition-dependent tunable bandgap as an advantage, suitable band alignment with the absorber layer is evaluated for equal or higher performance when compared to CdS. Further performance improvement is attempted by using SnSe as the back surface field (BSF) layer. Band alignment evaluation is also extended to the back contact (Mo)/SnSe interface, whereby an attempt is made to replace Mo with a suitable metal. The Ni is found as a good candidate to replace Mo to achieve high-efficiency solar cell. The same approach is repeated with the transparent conducting oxide layer, and aluminum doped zinc oxide (AZO) is found as a suitable material in place of ITO for optimized solar cell structure. A maximum power conversion efficiency of 17.55% is achieved with an optimized structure. It is also observed that the external quantum efficiency (EQE) of the solar cell is improved significantly in the blue photons region in comparison to the EQE of the champion solar cell. The optimized structure Ni/SnSe/CZT(S0.4 Se0.6 )/Zn(O0.3 S0.7 )/i-ZnO/AZO in this work will be very useful to fabricate low-cost and Cd-free high-efficiency kesterite solar cells.